PERIOPERATIVE EFFECTS OF INTRATHECAL CLONIDINE AND FENTANYL WITH HYPERBARIC BUPIVACAINE IN SPINAL ANESTHESIA FOR VAGINAL HYSTERECTOMY - Datta, Mallika; Chattopadhyay, Suman; Biswas, Biswanath (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objectives: Intrathecal fentanyl and clonidine are effective analgesics with different mechanisms of action. This study compares 25 Î¼g of both these drugs given intrathecally regarding onset, quality, and duration of hyperbaric bupivacaine-induced spinal block and side effects. Methods: A total of 90 patients of ASA I and II were randomly allocated into three equal groups. Group A received 0.5 ml of 0.9% normal saline (placebo), Group B and Group C received 25 Î¼g fentanyl and clonidine intrathecally added to 2.5 ml of 0.5% hyperbaric bupivacaine, respectively. The onset and regression time of sensory and motor blocks were recorded along with hemodynamic change, side effects, pain intensity (in terms of visual analog score (VAS), and time to first rescue analgesic. Results: Intrathecal clonidine (25 Î¼g) significantly prolongs sensory and motor blocks, with prolonged duration of analgesia in comparison with intrathecal fentanyl (25 Î¼g) (325Â±15 minutes vs. 240Â±7.6 minutes). VAS score was similar, but sedation was more in clonidine group. Conclusion: We conclude that low-dose intrathecal clonidine is an effective adjuvant to bupivacaine for spinal anesthesia and provides better postoperative analgesia in comparison with intrathecal fentanyl. Keywords: Clonidine, Fentanyl, Bupivacaine, Regional, Spinal, Postoperative pain.